The effect of socialization through the lens of Malay students on ethnic relations - Darshan Singh, Sarjit Singh; Badari, Shamsul Azahari Zainal; Yaccob, Yasmin; Radzlan, Rohaizahtulamni (Human Resource Management Academic Research Society, 2025)
This study examines the role of socialization agents—family, friends, and media—in shaping Malay students' attitudes and behaviours toward interethnic engagement in Malaysia. By exploring these domains of socialization, the research aims to uncover how each influences ethnic relations, fostering either cohesion or division. Using a quantitative approach, data were collected through an online survey targeting Malay students from diverse backgrounds. The findings reveal that family socialization significantly impacts initial perceptions of other ethnic groups, while peer interactions often challenge or reinforce these attitudes. Media, as a pervasive and dynamic influence, plays a dual role in either amplifying stereotypes or promoting intercultural understanding. This study contributes to understanding how socialization processes shape interethnic dynamics, offering insights for policymakers and educators to foster harmonious ethnic relations. The findings underscore the need for balanced and inclusive narratives across all domains of socialization to support a more integrated society